2020
DOI: 10.1002/cbin.11390
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin promotes tumor cells growth and drugs resistance through a CDC42‐YAP‐dependent signaling pathway in colorectal cancer

Abstract: Fibronectin (FN) is a high‐molecular‐weight glycoprotein of the extracellular matrix (ECM) that binds to membrane‐spanning receptor proteins or other elements in ECM. The expression of FN could be involved in the cancer cells proliferation or migration, and the molecular mechanisms responsible for FN induced protumor signals begin to be elucidated. Here, we report that the elevated expression of FN was observed in those chemoresistant tumor tissues from patients with colorectal cancer. Consistently, FN culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Interestingly, Fibronectin, a high-molecular-weight glycoprotein of ECM, was overexpressed in the ASM model. It has been reported that Fibronectin was observed in drug-resistant tumor tissues [35]. Fibronectin production occurred in the actual tumor microenvironment and appeared to promote drug resistance [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Fibronectin, a high-molecular-weight glycoprotein of ECM, was overexpressed in the ASM model. It has been reported that Fibronectin was observed in drug-resistant tumor tissues [35]. Fibronectin production occurred in the actual tumor microenvironment and appeared to promote drug resistance [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cilengitide has the most obvious antagonistic effect on cell adhesion to vitronectin compared to on laminin or fibronectin, which is consistent with our current results. In addition to α v β 3 , α v β 1 is also found as a receptor of vitronectin (Ding et al, 2002), whereas the main binding receptors of fibronectin are α v β 1 (Ye et al, 2020), α v β 6 (Mould et al, 2014), and α 5 β 1 (Mould et al, 2014) and the main binding receptor of laminin is α 6 β 1 (Corsini and Martin-Villalba, 2010). Previous research also confirmed that M21 human melanoma cells not only lost the ability to attach to vitronectin but showed a dramatic reduction in tumorigenicity when lacking integrin α v gene expression (Lacaria et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Hippo signaling pathway is dysregulated in numerous types of cancer, including CRC (32-34). Its inactivation is associated with CRC progression (35)(36)(37). YAP is a major effector in the Hippo signaling pathway and p-YAP exists in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%